Teaching Programming to Chemical Engineering Students - Riezqa Andika; Zulfan Adi Putra (ASEAN Journal of Science and Engineering Education, 2022)
Programming (including coding, data science, and artificial intelligence) is one of the important top skills for chemical engineering undergraduate students, especially in the current era of Industrial Revolution 4.0 (IR 4.0). Despite its importance, there is almost no dedicated course for programming in the traditional chemical engineering curriculum in many universities. In this article, a future chemical engineering curriculum that includes a programming course is discussed and its integration into traditional courses is also proposed. This study proposes to use three software i.e., Microsoft Excel, GAMS, and Python to make students comfortable to programming so they can learn further by themselves. A representative case of classic logistics problem is presented as a case study. It is expected that this teaching strategy and the proposed example will improve students’ cognition in programming.